Rethinking society and knowledge in Finnish social studies textbooks. Issue 6 (2nd November 2021) - Hansen, Petteri; Puustinen, Mikko
ABSTRACT: This paper discusses the relationship between knowledge and society in social studies by analysing how society is presented in four Finnish social studies textbooks currently in use in comprehensive education. Besides its empirical contribution, the paper examines the possibilities of applying Michael Young's understanding of powerful knowledge in social studies by complementing it with two additional theoretical approaches to society. Firstly, by applying Basil Bernstein's concept of recontextualisation, it is possible to elaborate on the way in which social studies textbooks reproduce societal power relations. Secondly, by observing the society of social studies textbooks in the light of Niklas Luhmann´s social systems theory, it is possible to examine how social reproduction in social studies is related to temporal forms of knowledge in a functionally differentiated, multifaceted society. The findings indicate that due to the present-focused and institutional approach to society, the textbooks offer few tools for critical understanding and for changing society.